With the release of electoral boundaries report, all eyes now on political parties’ next moves - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2020)
In a commentary, SMU Associate Professor of Law Eugene Tan discussed the implications of the Electoral Boundaries Review Committee (EBRC) report and what it means for the political parties and Singapore politics in general. He expects the election to be held sooner rather than later with the ERBC report's release, and there will be little time for parties, especially the opposition, to prepare.